29. EVALUATION OF THE EFFECTIVENESS OF THREAD-EMBEDDING ACUPUNCTURE COMBINED WITH ACUPRESSURE, ELECTROACUPUNCTURE, AND AQUAPUNCTURE IN THE TREATMENT OF KNEE OSTEOARTHRITIS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the pain-relieving and mobility-improving effects of thread-embedding acupuncture combined with acupressure, electroacupuncture, and aquapuncture in patients with knee osteoarthritis.Methods: A controlled, prospective clinical trial with pre- and post-treatment comparisons was conducted from May 2024 to June 2025 on 60 patients diagnosed with knee osteoarthritis and treated at the Department of Traditional Medicine, Military Hospital 103.Results: After 15 days of treatment, there was a significant improvement in VAS scores, Lequesne index, knee flexion range of motion, and heel-to-buttock distance compared to baseline (p < 0.05) in both groups. The degree of improvement in these indices was greater in the study group and showed statistically significant differences compared to the control group (p < 0.05).Conclusion: The combination of thread-embedding acupuncture, acupressure, electroacupuncture, and aquapuncture was effective in reducing pain and improving joint mobility and Lequesne index scores in patients with knee osteoarthritis.
Keywords: Knee osteoarthritis; thread-embedding acupuncture; acupressure; electroacupuncture; aquapuncture.